Spatial self-organization of confined bacterial suspensions - Babak Vajdi Hokmabad; Alejandro Martínez-Calvo; Sebastian Gonzalez La Corte; Sujit S. Datta (Proceedings of the National Academy of Sciences, 2025)
Lab studies of bacteria usually focus on cells in spatially extended, nutrient-replete settings, such as in liquid cultures and on agar surfaces. By contrast, many biological and environmental settings—ranging from mucus in the body to ocean sediments and the soil beneath our feet—feature multicellular bacterial populations that are confined to tight spots where essential metabolic substrates (e.g., oxygen) are scarce. What influence does such confinement have on a bacterial population? Here, we address this question by studying suspensions of motile Escherichia coli confined to quasi two-dimensional (2D) droplets. We find that when the droplet size and cell concentration are both large enough, the initially uniform suspension spatially self-organizes into a concentrated, immotile inner “core” that coexists with a more dilute, highly motile surrounding “shell.” By simultaneously measuring cell concentration, oxygen concentration, and motility-generated fluid flow, we show that this behavior arises from the interplay between oxygen transport through the droplet from its boundary, uptake by the cells, and corresponding changes in their motility in response to oxygen variations. Furthermore, we use biophysical theory and simulations to quantitatively describe this interplay. Our work thus sheds light on the rich collective behaviors that emerge for bacterial populations in confined environments, with implications for understanding ecological niches and engineering artificial systems.